(untitled) (Economic and Political Thought, 2017)
The main aim of this article is to present the results of empirical research into the factors and their impact on the efficiency of supervisory boards in municipally owned companies. The first part defines the concept of a municipally owned company. Next, the importance and role of a supervisory board in a company is characterised. In the second part, the concept of supervisory board efficiency is formulated and factors determining it are identified. The author also presents the results of his study into the impact of selected factors on the efficiency of supervisory boards of municipally owned companies surveyed. The conclusions are based on the study of literature and a questionnaire completed by three groups of respondents.